Book Reviews. (1st August 2013) - Keating, Patrick; Aspell, Luke; Mustafa, Suzan Ashleigh; Khelifa, Nadja Ben; Buckle, Luke; Conterio, Martyn; Robinson, Matthew S.; Sayed, Yusef
Love in the Time of Cinema, Kristi McKim, (2012) New York: Palgrave Macmillan, 208 pp., ISBN 9780230301368 (hbk), $90.00Thomas Ince: Hollywood's Independent Pioneer (Screen Classics), Brian Taves, (2011) Lexington: University Press of Kentucky, 368 pp., ISBN 9780813134222 (hbk), $39.95Greek Cinema: Texts, Histories, Identities, Lydia Papadimitriou and Yannis Tzioumakis (eds), (2012) Bristol: Intellect Ltd, 279 pp., ISBN 9781841504339 (pbk), £24.95, $40Scotland: Global Cinema – Genres, Modes and Identities, David Martin-Jones, (2009) Edinburgh: Edinburgh University Press, 254 pp., ISBN 9780748633913 (hbk), £70.00Brutal Vision: The Neorealist Body in Postwar Italian Cinema, Karl Schoonover, (2012) Minneapolis and London: University of Minnesota Press, 283 pp., ISBN 9780816675555 (pbk), £18.50; ISBN 9780816675546 (hbk), £55.00World Film Locations: London, Neil Mitchell (ed.), (2011) Bristol: Intellect, 136 pp., ISBN 9781841504841 (pbk), £11.50Popular Italian Cinema: Culture and Politics in a Postwar Society, Flavia Brizio-Skov, (2011) London: I.B. Tauris, 255 pp., ISBN 9781848855724 (hbk), £50.58Virtual Hallyu: Korean Cinema of the Global Era, Kyung Hyun Kim, (2011) Durham, NC: Duke University Press, 255 pp., ISBN 9780822351016 (pbk), $24.95; ISBN 9780822350880 (hbk), $89.95